(3GdJUeje GdOGNdi GdeSJOGe HJWHjb fXGe Jbjje (BLEED =s sustainable interior design by application of lle rating system - (3QgGe GjgGH Ndjds; (3jGSQ SjO GdHOhis; (3YGOd YOdi GHQGgjes; (3LGeYI MdhGf(B.s (3cdjI Gdafhf GdJWHjbjI(B.s (3bSe GdJUeje GdOGNdi h GdGKGK(B.s ((3LGeYI MdhGf ;s (3cdjI Gdafhf GdJWHjbjI (B. (3bSe GdJUeje GdOGNdi h GdGKGK(B.s, 2016)
(3hef GdGgOGa (B:(3gh GdJYQja HGdJLgGJ GdMOjKI ddJUeje GdHjFi ai GhGNQ GdbQf Gd(B20 (3h HOGjI (B21. (3GdefgL GdeSJNOe(B: (3GdhUai GdJMdjdi hef GdfJGFL (B:1. (3GJLGI GdGSJOGeI ai GdMjRGJ GdOGNdjI GdaQGZjI ef Gge GdGJLGgGJ GdJi JMGaX Ydi GdWGbI Yf WQjb Jbdjd eYOdGJ GSJgdGcgGs
(3GWQhMI (B((3eGLSJjQ (B) - (3LGeYI MdhGf(B. (3cdjI Gdafhf GdJWHjbjI (B. (3bSe GdJUeje GdOGNdi h GdGKGK(B.s
(3JTJed Ydi EQLGYGJ HHdjhLQGajI (B((3U(B.569 - 609)s
(3GdfU HGddZI GdYQHjI(B, (3GdedNU HGddZI GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdGKGK(B.s